Factors That Influence the Occurrence of Hypertension in The Puskesmas Ogoamas, North Sojol, Donggala in 2024 - Haeruddin; Sudirman; Lestari, Ayu (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2025)
This research aims to determine "Factors that Influence the Occurrence of Hypertension in ​​the Puskesmas Ogoamas in 2024". This research uses a cross-sectional method with sampling techniques, Accidental Sampling with a sample size of 55 people who visited the Puskesma Ogoamas . Analysis using tests Chi-Square where three factors have a relationship, namely family history, the most common being no history of hypertension, amounting to 32 people (58.2%) with a value of Ꝭ value 0.015 (α<0.05), then the most non-smokers were 36 people (65.5%) with a value of Ꝭ value 0.040 (α<0.05), then the most hypertension screening was 39 people (70.9%) with a p value value 0.038 (α<0.05). Factors that Influence the Occurrence of Hypertension in the Working Area of ​​the Puskesma Ogoamas in 2024, namely family history, gender, smoking, hypertension screening and hypertension. The incidence of hypertension in the Ogoamas Community Health Center Working Area, North Sojol District, Donggala Regency in 2024 is related to family history, smoking and hypertension screening. The recommended intervention is for respondents to regularly control their blood pressure and have their health checked at the nearest health service facility and increase information through various media about health that can be useful.